2004
DOI: 10.1159/000081896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Granulocyte and Monocyte Adsorption Apheresis on Urinary Albumin Excretion and Plasma Endothelin-1 Concentration in Patients with Active Ulcerative Colitis

Abstract: Background/Aim: Increases in microalbuminuria and endothelin (ET-1) are involved in the development of ulcerative colitis (UC) and in its progress. Because granulocyte and monocyte adsorption apheresis has proven to be useful in the treatment of UC, we examined whether urinary albumin excretion and plasma ET-1 concentrations are altered and whether granulocyte and monocyte adsorption apheresis affects the concentrations of these two factors in patients with active UC. Methods: Twenty patients with active UC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The results after 6 weeks show moderate heterogeneity (I 2 = 63%), but sensitivity analyses do not provide an explanation for this heterogeneity. There was some nonsignificant evidence of publication bias, but this finding was mainly due to the extremely positive results in one trial [17].…”
Section: Response Remission and Relapse Ratesmentioning
confidence: 94%
See 1 more Smart Citation
“…The results after 6 weeks show moderate heterogeneity (I 2 = 63%), but sensitivity analyses do not provide an explanation for this heterogeneity. There was some nonsignificant evidence of publication bias, but this finding was mainly due to the extremely positive results in one trial [17].…”
Section: Response Remission and Relapse Ratesmentioning
confidence: 94%
“…In three other trials, the protocol dictated that medications administered concurrently were to remain unchanged [15,17,21]. Only in the two trials by Hanai et al [19] was concurrent steroid medication increased or decreased in line with the clinical course of the disease.…”
Section: Clinical Response or Remission After 12 Weeksmentioning
confidence: 99%
“…Individual trial characteristics are provided in Table 1. Four trials compared GMAA with conventional medical therapy, 24, 25, 31, 32 two separate trials (reported in a single article) compared GMAA with sham apheresis 26 and four trials compared ‘intensive’ vs. ‘conventional’ GMAA regimens 27–30 . Only two trials were at low risk of bias according to our assessment 26 .…”
Section: Resultsmentioning
confidence: 98%
“…The search strategy identified a total of 1729 citations, 16 of which appeared to be relevant to the study question, and were therefore retrieved and evaluated in more detail (Figure 1). Nine articles, 24–32 reporting the results of ten separate RCTs, were eligible for inclusion in the systematic review. We did not perform a formal meta‐analysis due to concerns about the high risk of bias among the RCTs we identified.…”
Section: Resultsmentioning
confidence: 99%
“…Extremely positive results have been reported using this method for the treatment of ulcerative colitis in Japan,6–13 but results obtained in Europe and the US have been more contradictory 1419. Nevertheless, a recent meta-analysis20 pooling data from seven randomized controlled trials 6,9,17,2124 clearly demonstrated the benefits of this method with respect to control treatments for the induction of remission or response at week 12. On the other hand, the only sham-controlled randomized controlled trial, in a slightly to moderately ill population, did not show a statistically significant difference between sham and active treatment 24…”
Section: Introductionmentioning
confidence: 99%